5. Complete the following. a) Simplify: i) \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \) ii) \( \left(m+\frac{1}{m}\right)^{2} \). b) If \( m+\frac{1}{m}=2 \), calculate the value of: i) \( m^{2}+\frac{1}{m^{2}} \) ii) \( m^{3}+\frac{1}{m^{3}} \)
Real Tutor Solution
Answer
Solution
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To tackle these problems, let's simplify and calculate step by step. a) i) First, simplify \( \left(m+\frac{1}{m}\right)\left(m^{2}-1+\frac{1}{m^{2}}\right) \). Starting with the first expression: \[ m^2 - 1 + \frac{1}{m^2} = (m^2 + \frac{1}{m^2}) - 1 \] Now, we recognize that \( m^2 + \frac{1}{m^2} \) can be derived from the identity \( (m + \frac{1}{m})^2 = m^2 + 2 + \frac{1}{m^2} \), so \( m^2 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 \). Then we substitute: \[ m^2 - 1 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 3 \] Substituting back, we get: \[ \left(m+\frac{1}{m}\right)\left((m+\frac{1}{m})^2 - 3\right) \] Let \( x = m+\frac{1}{m} \): \[ x (x^2 - 3) = x^3 - 3x \] ii) For \( \left(m+\frac{1}{m}\right)^{2} \): \[ \left(m+\frac{1}{m}\right)^{2} = m^2 + 2 + \frac{1}{m^2} \] So, it simplifies directly to: \[ m^2 + \frac{1}{m^2} + 2 \] b) i) If \( m+\frac{1}{m}=2 \), then substituting into the derived formula: \[ m^2 + \frac{1}{m^2} = (m+\frac{1}{m})^2 - 2 = 2^2 - 2 = 4 - 2 = 2 \] ii) To find \( m^{3}+\frac{1}{m^{3}} \), use the identity: \[ m^{3}+\frac{1}{m^{3}} = \left(m+\frac{1}{m}\right) \left(m^{2}+\frac{1}{m^{2}}\right) - (m+\frac{1}{m}) \] Substituting values: \[ m^{3}+\frac{1}{m^{3}} = 2 \cdot 2 - 2 = 4 - 2 = 2 \] Thus, summarizing the results: a) i) \( x^3 - 3x \) ii) \( m^2 + \frac{1}{m^2} + 2 \) b) i) 2 ii) 2